Analysis of refraction and prevalence of myopia among school-age children in Nantong City from 2019 to 2020 - Wang, Min; Zhou, Yue; Xiong, Yao Jia; Sun, Zhi Min (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse the refractive status and prevalence of myopia among school-age children. Method: The prospective, school-based study was conducted from September 2019 to September 2020 in Nantong, China, and comprised students from two primary and as many middle and high schools from which two classes were chosen from each grade. Ophthalmic examinations were conducted one year apart, and included measurements of refraction and vision. Data was analysed using SPSS 22. Results: Of the 1,787 students, 959(53.7%) were boys. The overall mean age was 10.55±3.19 years. The uncorrected visual acuity of the students was lower in 2020 than in 2019, with the right eye visual acuity decreasing by 0.08±0.48. There was no significant association between gender and uncorrected visual acuity. The changes in uncorrected visual acuity, sphere and spherical equivalent refraction between the ages of 7 and 12 years were significant (p<0.05). Among those aged 6-17 years, the prevalence of myopia was higher in 2020 than in 2019 (p<0.001). At the age of 10 years, the spherical equivalent refraction decreased the most (by -0.66 D, p<0.001; Figure 2), and visual acuity decreased the most at the age of 12 years (by -0.21, p<0.001; Figure 1). Conclusion: One year from the baseline, the students’ refraction showed a myopic drift, and their uncorrected visual acuity declined. The apparent change in spherical equivalent refraction occurred two years before the decline in visual acuity. Key Words: Myopia, Prevalence, Refraction, Vision, School-age children.